Модернізація агломераційної фабрики ПрАТ «КАМЕТ-СТАЛЬ»: організаційні, технологічні, екологічні та техніко-економічні аспекти - Воденнікова, О.С.; Воденніков, С.А.; Бондаренко, Я.В. (Physico-technological Institute of Metals and Alloys, 2024)
A short-term industrial project of modernization of the agglomeration factory of PJSC “KAMET-STEEL” (Ukraine, Kamianske) is proposed. The implementation of the project is carried out in three directions — improvement of agglomerate sintering technology, overhaul of agglomeration machine No. 7 and improvement of the gas purification process of process gases and aspiration of the main dust removal units. The implementation of the project involves the following stages: engineering works; supply of equipment and production of technological metal structures; construction and assembly works and putting the modernized agglomeration machine into operation. For the capital repair of agglomeration machine No. 7, it is proposed to carry out: repair of the longitudinal and transverse seals of the agglomeration machine; repair of the gas collector, vacuum chambers, dust bags, compensators in the sintering zone, vacuum chambers in the cooling zone; restoration of thermal insulation on the gas collector, vacuum chambers, dust bags. For the purification of process gases at the sintering plant of PJSC “KAMET-STEEL” it is proposed to: replace the exhauster; installation of a new gas treatment; improvement of aspiration systems; dismantling of quenching and return cooling drums. An opportunity is shown by improving the process of gas purification of process gases and aspiration of the main dust removal units, to achieve a dust content of no more than 30 mg/m3, a CO content — of up to 6500 mg/m3, an SOx content — of no more than 500 mg/m3, and to reduce the overall dustiness at the sintering plant by 20 %. The technical and economic substantiation of the feasibility of modernization of the agglomeration factory of PJSC “KAMET-STEEL” is given. It has been established that the introduction of agglomerate sintering technology due to the use of energy-saving measures will lead to a 1.08 % decrease in the cost of 1 ton of agglomerate, which in turn will affect the decrease in the cost of 1 ton of cast iron.